Students satisfaction in using UiTM MOOC platform for e-learning / Siti Noorbaini Sarmin …[et al.] - Sarmin, Siti Noorbaini; Akmal Saad, Zuria; Mohamad, Noorshashillawati Azura; Abdullah, Zaimatul Aqmar (Universiti Teknologi MARA Cawangan Pahang, 2021)
Within only a few years, the use of e-Learning has increased rapidly in Universiti Teknologi MARA (UiTM), Malaysia. Following the empowering improvement, Massive Open Online Course (MOOC) using UiTM platform has been introduced in the mid-year of 2019. Nevertheless, which aspects of e-Learning do students consider significant for their learning accomplishments and course fulfillment? This question was addressed by surveying 108 students about their expectations of, and experiences in e-Learning using UiTM MOOC platform. Concerning on their expectations as well as aspects of benefits towards e-Learning, the flexibility of learning places was ranked higher than other aids of e-Learning. With regard to their experience and aspects of easy use of the interface, the UiTM MOOC platform was simply accessible and visually attractive. The results also show that the lack of internet connection can interrupt their concentration and motivation. The findings provide insight into those factors that are likely significant antecedents for planning and implementing an e-Learning system to enhance student learning satisfaction.